Respiration Dynamics and a Rapid Colorimetric Assay for Seed Vigour Assessment in Paddy and Lentil - Naik , Manja E.; Kumar, Rajeev; Singh, Deepak; Vijay, D.; Singh, Chandu; Vijayakumar, H. P.; Yalamalle, V. R. (International Journal of Bio-resource and Stress Management, 2026)
The experiment was conducted during October, 2024–June, 2025 at Indian Agricultural Research Institute, New Delhi to study seed respiration and vigour assessment in lentil and paddy. Seed respiration was one of the earliest metabolic activities recorded in the imbibed seeds. Seed ageing impairs cellular function, leading to reduced respiration. This study evaluated CO2 evolution in three seed lots, each of paddy and lentil, using an infrared CO2 sensor. Lentil exhibited the highest CO2 evolution (854.93 ppm seed-1), while paddy recorded the lowest CO2 evolution (429.65 ppm seed-1). Significant within-crop variation was observed. In lentil, the lot L-4727(23-24), which had the highest germination, also recorded the highest CO2 release (1034.73 ppm seed-1), whereas L-4727(19-20) showed the lowest (707.87 ppm seed-1). Similarly, in paddy, PB 1847 recorded the highest CO2 evolution (446.69 ppm seed-1) and PB 1985 recorded the lowest (418.77 ppm seed-1). A rapid colorimetric vigour test was developed by trapping the CO2 in the bromothymol blue (BTB) solution. OD430 values showed strong correlations with vigour index-I (R²=0.96) and vigour index-II (R²=0.93) in paddy and with vigour index-I (R²= 0.98) and vigour index-II (R²=0.76) in lentil. High-vigour seeds consistently exhibited higher respiration rates and higher OD430 values, validating BTB as a reliable indicator for vigour assessment. The present study presented a novel respiration-based rapid colorimetric vigour test capable of distinguishing seed lot vigour within 7 h.